The nexus between health and economy: evidence from Malaysia / Wong Sing Yun and Jain Yassin - Wong, Sing Yun; Yassin, Jain (Faculty of Business and Management, 2022)
With the recent spread of the pandemic that has disrupted global economic activities, this paper seeks to explore the causal relationship between health outcomes and the socioeconomic indicators in Malaysia. Besides that, this paper will evaluate the income-health relationship in determining empirically whether this hypothesis is likely to hold in Malaysia. Empirical evidence from this paper highlighted a bi-directional causality between life expectancy and economic growth. Comprehension of such true causal relationship will be crucial to determine the direction of the flows. The findings from this study will provides additional insights into the relationship between economic changes and health indicator.